MOTIVASI DAN SIKAPAPOTEKER DALAM PENGENDALIAN PERSEDIAAN FARMASI DI APOTEK KOTA PALU - Diana, Khusnul; Rinaldhi Tandah, Muhamad; Dibyo, Arya; Putri, Meliani (Akademi Farmasi Indonesia Yogyakarta, 2022)
Pharmaceutical supplies are the main commodity in the pharmaceutical sector in service facilities, one of which is a pharmacy. Controlling pharmaceutical supplies in pharmacies is one of the duties and responsibilities of a pharmacist managing a pharmacy (APA). The task can run well if the pharmacist has high motivation and a good attitude in controlling pharmaceutical inventory. This study aimed to measure the attitude and motivation of pharmacists in inventory control and how the influence of motivation on attitudes in managing pharmaceutical inventory in pharmacies. This type of research is a descriptive observational study with cross-sectional data collection. The sample used is pharmacist managing pharmacies (APA) in pharmacies in Palu City as many as 73 respondents. The attitude and motivation of pharmacists were measured using a questionnaire that had been tested for validity and reliability. The results of the respondent's data were analyzed descriptively and a simple linear regression test. The outcome on the measurement of pharmacist motivation was dominated by the moderate category, with as many as 51 respondents (69.86%). The results of measuring the attitude of pharmacists in controlling pharmaceutical inventory in pharmacies are dominated in the good category as many as 36 respondents (49.32%). With a simple regression test, the tcount value is 0.783 (< ttable = 1.66), which means that there is no significant effect between motivation on the attitude of the pharmacist. The linear regression equation is Y=39,527+0,151X, meaning that if the motivation value increases by 1, the attitude will increase by 0.151. It can be concluded that the attitude in controlling pharmaceutical inventory by pharmacists in pharmacies is not influenced by motivation.